Clinical-Laboratory Examination of Dental Diseases in Chemical Industry Workers (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2024)
The question of negative conditions in the oral cavity of workers in the chemical industry remains relevant. It has been proven that the high prevalence of non-carious lesions of the teeth and oral mucosa is associated with production processes such as oil and gas extraction, metallurgy, chemical production, baking and confectionery.